Die philosophischen Aspekte von Mark Aldanovs Werk - Setschkareff, Vsevolod (Vortraege und Abhandlungen zur Slavistik, 1996)
Although Aldanov's novels were very successful during the first Russian emigration and were translated into many languages, he fell into oblivion for some unknown reason. They are embedded in the story, play within the story, d. H. they include the contemporary political events as mental experiences of the persons. Aldanov knows how to give them an overall symbolic meaning in addition to their own lives - in fact: "They explain their epoch as the epoch explains it."